Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
Step-by-step explanation:
1)
Given that:
The joint pmf [tex]p_{X,Y(a,b)}=\left \{ {{\dfrac{1}{4a} \ for \ 1 \le b \le a \le 4 } \\ \\ \atop {0} \ \ \ \ \ \ otherwise} } \right.[/tex]
To emphasize that this is a joint pmf;
We will notice that it obeys two conditions;
- it comprises a non-negative number and which is less than 1
- the sum of all the probabilities adds up and becomes unity.
Except that X and Y are integer value variables with 1 ≤ b ≤ a ≤ 4 and X = 1, 2, 3, 4 and Y = 1, 2, 3, 4 respectively, according to the condition Y ≤ X
The table below shows the joint probabilities as a result of this:
y = 1 y = 2 y = 1 y = 4 Total
x = 1 [tex]\dfrac{1}{4}[/tex] 0 0 0 [tex]\dfrac{1}{4}[/tex]
x = 2 [tex]\dfrac{1}{8}[/tex] [tex]\dfrac{1}{8}[/tex] 0 0 [tex]\dfrac{1}{4}[/tex]
x = 3 [tex]\dfrac{1}{12}[/tex] [tex]\dfrac{1}{12}[/tex] [tex]\dfrac{1}{12}[/tex] 0 [tex]\dfrac{1}{4}[/tex]
x = 4 [tex]\dfrac{1}{16}[/tex] [tex]\dfrac{1}{16}[/tex] [tex]\dfrac{1}{16}[/tex] [tex]\dfrac{1}{16}[/tex] [tex]\dfrac{1}{4}[/tex]
Total [tex]\dfrac{25}{48}[/tex] [tex]\dfrac{13}{48}[/tex] [tex]\dfrac{7}{48}[/tex] [tex]\dfrac{3}{48}[/tex] 1
In the table, it is obvious that each respective value of the probability is positive and the addition of all the values sums up to unity (1).
Hence, the given probability shows that it is indeed a pmf(probability mass function).
(b)
Marginal Pmf of x = [tex]\dfrac{sum \ of \ all \ prob. \ of (x,y)}{y}[/tex]
Marginal Pmf of y = [tex]\dfrac{sum \ of \ all \ prob. \ of (x,y)}{x}[/tex]
Thus, we can locate the respective values of the marginal probability in the last row as well as the last column in the explained table above.
(c)
To find P(X=Y+1):
P(X = Y + 1) = P(X = 2,3,4)
⇒ 1 - P(X=1)
[tex]\implies 1 - \dfrac{1}{4} \\ \\ \implies \dfrac{4-1}{4} \\ \\ \implies \dfrac{3}{4}[/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.